2001
DOI: 10.1055/s-2001-15263
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Motor Neuron Disease and Related Motor Syndromes

Abstract: There is an imperative need for the early diagnosis of amyotrophic lateral sclerosis/motor neuron disease (ALS/MND) in the current era of emerging treatments. When evaluating the patient with ALS/MND, the neurologist must consider a number of other motor neuron disorders and related motor syndromes that may have clinical features resembling ALS/MND. The revised Airlie House-El Escorial diagnostic criteria have been established through the consensus of experts meeting at workshops. However, by definition, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 69 publications
(99 reference statements)
0
14
0
1
Order By: Relevance
“…Although this diagnostic category may be largely represented by progressive muscular atrophy (PMA) and there are reports defining pure sporadic lower motor neuron disease as a separate nosographic entity, 15 still PMA can be considered as part of the spectrum of ALS because neurophysiologic and pathologic studies detect pyramidal tract involvement in patients with LMN signs, 16,17 and ubiquinated inclusions (typical ALS findings) have been found in most PMA cases. 17 In addition, patients with familial ALS carrying different superoxide dismutase-1 mutations present at the onset with a LMN phenotype 18,19 and are included in the revised El Escorial categories as clinically definite familial, laboratory-supported ALS.…”
Section: Discussionmentioning
confidence: 98%
“…Although this diagnostic category may be largely represented by progressive muscular atrophy (PMA) and there are reports defining pure sporadic lower motor neuron disease as a separate nosographic entity, 15 still PMA can be considered as part of the spectrum of ALS because neurophysiologic and pathologic studies detect pyramidal tract involvement in patients with LMN signs, 16,17 and ubiquinated inclusions (typical ALS findings) have been found in most PMA cases. 17 In addition, patients with familial ALS carrying different superoxide dismutase-1 mutations present at the onset with a LMN phenotype 18,19 and are included in the revised El Escorial categories as clinically definite familial, laboratory-supported ALS.…”
Section: Discussionmentioning
confidence: 98%
“…Neurophysiological and autopsy studies demonstrated that the pyramidal tracts are often affected in patients with LMN syndromes [18,19] and ubiquinated inclusions typical of ALS have been found in most PMA cases in a recent report [19]. Familial cases carrying superoxide dismutase-1 mutations frequently present LMN phenotype at onset [20,21].…”
Section: Classification Of Cases and Entry In Clinical Trialsmentioning
confidence: 96%
“…6 The pattern of muscle weakness in our patient is also typical of MA, which is characterized most frequently by involvement of the C8/T1 myotomes. 3,7,9,10 The weakness is restricted to the single presenting extremity in most cases, but a small number of patients have milder involvement of the contralateral limb clinically, electrodiagnostically, and/or by imaging studies. 5,7,9,11 Neuroimaging of some patients with MA may reveal focal cord atrophy or lack of the normal cervical enlargement.…”
Section: Discussionmentioning
confidence: 99%